2021
DOI: 10.1101/2021.03.17.435838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A distinct assembly pathway of the human 39S late pre-mitoribosome

Abstract: Assembly of the mitoribosome is largely enigmatic and involves numerous assembly factors. However, little is known about their function and the architectural transitions of the pre-ribosomal intermediates. Here, we solved cryo-EM structures of the human 39S large subunit pre-ribosomes, representing four distinct late state intermediates. Besides the MALSU1 complex, we identified several assembly factors, including the DDX28 helicase, MRM3, GTPBP10 and the NSUN4-mTERF4 complex, all of which keep the 16S rRNA in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 58 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…The studies, however, differ notably in the precise step during assembly, the biogenesis factors recruited, and finally, the GTPase in control. The deleterious consequences of manipulating NSUN4 or MTERF4 binding to the mitoribosome in vivo illustrate the importance of these proteins in mediating not only the exact step during PTC maturation that we have trapped, but also the prior and subsequent steps described in Cheng et al, 2021 ; Cipullo et al, 2021 ; Hillen et al, 2021 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The studies, however, differ notably in the precise step during assembly, the biogenesis factors recruited, and finally, the GTPase in control. The deleterious consequences of manipulating NSUN4 or MTERF4 binding to the mitoribosome in vivo illustrate the importance of these proteins in mediating not only the exact step during PTC maturation that we have trapped, but also the prior and subsequent steps described in Cheng et al, 2021 ; Cipullo et al, 2021 ; Hillen et al, 2021 .…”
Section: Discussionmentioning
confidence: 89%
“…A comprehensive review of GTPases in human mitoribosomal assembly ( Maiti et al, 2021 ) and four studies describing cryo-EM structures of mtLSU late assembly intermediates distinct from ours and from each other ( Cheng et al, 2021 ; Cipullo et al, 2021 ; Hillen et al, 2021 ; Lenarčič et al, 2021 ), appeared during manuscript preparation. All five studies, including ours, have trapped MALSU1·L0R8F8·mt-ACP and NSUN4·MTERF4 at the same location on the mtLSU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the methylation of 16S mt-rRNA nucleotides in MRM1-3 knock-out models showed that the 2'-O-methylation of U1369 by MRM2 depends on the prior modification of U1370, substrate of MRM3 (Figure 1). This implies that MRM3 exerts its activity over the assembling mtLSU prior to MRM2, adding molecular evidence to support structural findings (Chandrasekaran et al, 2021;Cheng et al, 2021;Hillen et al, 2021;Lenarčič et al, 2021).…”
Section: Discussionmentioning
confidence: 55%
“…The late stages of mtLSU assembly involve almost exclusively the remodelling of interfacial RNA elements of otherwise complete particles, as shown by recent structural studies (Chandrasekaran et al, 2021;Cheng et al, 2021;Hillen et al, 2021;Lenarčič et al, 2021). Key players include the helicase DDX28, which dislocates the central protuberance to increase solvent exposure of the intersubunit interface, the MTERF4:NSUN4 complex, which holds H68-71 of domain IV of 16S mt-rRNA in an immature conformation to allow access of assembly factors to the PTC, and the GTPases GTPBP5, GTPBP6, GTPBP7 and GTPBP10, which coordinate the maturation of the PTC through a series of conformational rearrangements.…”
Section: Discussionmentioning
confidence: 94%